Influence of Ordinary Cigarettes and Their Substitute IQOS® on Secretory Immunoglobulin A in Unstimulated Saliva - Niкolai Pavlov; Ivelina Popova-Sotirova; Nina Musurlieva; Ralitsa Raycheva; Konstantin Trifonov; Maria Atanasova; Radka Cholakova (Dentistry Journal, 2025)
Background: Secretory immunoglobulin A (sIgA) plays a key role in oral and mucosal immunity, serving as a first-line defense against pathogens. Smoking is known to negatively affect immune function, but data on the impact of heated tobacco products such as IQOS® on sIgA levels are limited. Objective: To assess and compare the effects of conventional cigarette smoking and IQOS® use on the concentration of salivary sIgA in healthy individuals. Methods: A total of 200 participants were enrolled and divided into three groups: 60 non-smokers, 70 conventional cigarette smokers, and 70 IQOS® users. Unstimulated whole saliva samples were collected and analyzed for sIgA concentration using ELISA method. Statistical analysis was performed using IBM SPSS Statistics 25. Results: Mean salivary sIgA levels were significantly lower in both cigarette smokers (246.03 μg/mL) and IQOS® users (243.54 μg/mL) compared to non-smokers (380.74 μg/mL, p < 0.05). No significant difference was observed between cigarette smokers and IQOS® users. A pronounced reduction in sIgA was seen in female users of both tobacco products, whereas male users did not show a statistically significant decline. Conclusions: Both cigarette smoking and IQOS® use are associated with a significant decrease in salivary sIgA levels, particularly in females. The findings suggest that IQOS® does not offer an immunological advantage over conventional smoking in terms of preserving mucosal immunity. Further studies are needed to confirm these findings and explore underlying mechanisms.